2012
DOI: 10.5142/jgr.2012.36.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophytes from Three Cultivars of Panax ginseng Meyer Cultivated in Korea

Abstract: In order to investigate the diversity of endophytes, fungal endophytes in Panax ginseng Meyer cultivated in Korea were isolated and identified using internal transcribed spacer (ITS) sequences of ribosomal DNA. Three cultivars of 3-year-old ginseng roots (Chunpoong, Yunpoong, and Gumpoong) were used to isolate fungal endophytes. Surface sterilized ginseng roots were placed on potato dextrose agar plates supplemented with ampicilin and streptomycin to inhibit bacterial growth. Overall, 38 fungal endophytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The host materials were all healthy in this study. Park et al ( 2012) reported that Phoma radicina , Fusarium oxysporum , Setophoma terrestris and Ascomycota were the predominant endophytic fungi in Korean Ginseng, and Xing et al ( 2010) reported that Cladosporium sp. was the dominant species in the root of Panax quinquefolium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host materials were all healthy in this study. Park et al ( 2012) reported that Phoma radicina , Fusarium oxysporum , Setophoma terrestris and Ascomycota were the predominant endophytic fungi in Korean Ginseng, and Xing et al ( 2010) reported that Cladosporium sp. was the dominant species in the root of Panax quinquefolium .…”
Section: Discussionmentioning
confidence: 99%
“…2-RNK. The most dominant fungal endophyte was P. radicina 2012). In the present study, to select the endophytes with the capacity of producing saponins, we investigated the diversity of the endophytic fungi in the roots of Panax ginseng cultivated in the forest of Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi were isolated from ginseng plants of various ages, as well as different tissues, cultivars and locations in previous studies (Park et al, 2012a;2012b;2012c) (Supplementary Table S1). In this study, forty previously identified endophytic fungi were screened for antimicrobial activity against ginseng pathogens.…”
Section: Endophytic Fungi and Ginseng Pathogensmentioning
confidence: 99%
“…In previous studies, forty species of endophytic fungi were isolated from various tissues of ginseng plants (Park et al, 2012a;2012b;2012c). Six of these were selected by preliminary screening against six ginseng pathogens for further antimicrobial activity tests (Table 1 and Supplementary Fig.…”
Section: Antimicrobial Activities Of Endophytic Fungi Against Ginsengmentioning
confidence: 99%
“…Studies found that 51 bacteria were isolated from the Korean Ginseng, which at different ages could promote the growth of the ginseng [13,14]. The ginseng endophytic fungi was isolated and identified as well [15,16]. The endophytes called Bacillus polymyxa which was isolated from the fresh ginseng has been screened by our laboratory and this strain could significantly improve the ginsenosides concentration [17].…”
Section: Introductionmentioning
confidence: 98%